Model to Determine Risk of Pancreatic Cancer in Patients with New-onset Diabetes - Sharma, Ayush (Gastroenterology, 2018)
BACKGROUND & AIMS: Of subjects with new-onset diabetes (based on glycemia) over the age of 50 years, approximately 1% are diagnosed with pancreatic cancer within 3 years. We aimed to develop and validate a model to determine risk of pancreatic cancer in individuals with new-onset diabetes. METHODS: We retrospectively collected data from 4 independent, non-overlapping cohorts of patients (n=1561) with new-onset diabetes (based on glycemia; data collected at date of diagnosis and 12 months before) in the Rochester Epidemiology Project, from January 1, 2000 through December 31, 2015 to create our model. The model weighed scores for the 3 factors identified in the discovery cohort to be most strongly associated with pancreatic cancer (64 patients with pancreatic cancer and 192 with type-2 diabetes): change in weight, change in blood glucose, and age at onset of diabetes. We called our model enriching new-onset diabetes for pancreatic cancer (END-PAC). We validated the locked-down model and cutoff score in an independent population-based cohort of 1096 patients with diabetes; of these 9 patients (.82%) had pancreatic within 3 years of meeting the criteria for new-onset diabetes. RESULTS: In the discovery cohort the END-PAC model identified patients who developed pancreatic cancer within 3 years of onset of diabetes with an area under the receiver operating characteristic curve value of 0.87; a score of ≥3 identified patients who developed pancreatic cancer with 80% sensitivity and specificity. In the validation cohort, a score of ≥3 identified 7/9 patients with pancreatic cancer (78%), with 85% specificity; the prevalence of pancreatic cancer in subjects with score of ≥3 (3.6%) was 4.4-fold more than in patients with new-onset diabetes. A high END-PAC score in subjects who did not have pancreatic cancer (false positives) was often due to such factors as recent steroid use or different malignancy. An END-PAC score <0 (in 49% of subjects) meant that patients had an extremely low-risk for pancreatic cancer. An END-PAC score ≥3 identified 75% of subjects in the discovery cohort >6 months before a diagnosis of pancreatic cancer. CONCLUSIONS: Based on change in weight, change in blood glucose, and age at onset of diabetes, we developed and validated a model to determine risk of pancreatic cancer in patients with new-onset diabetes, based on glycemia (the END-PAC model). An independent, prospective study is needed to further validate this model, which could contribute to early detection of pancreatic cancer.